(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Microcontroller Unit (MCU) Based Trash Remover is a device that can remove solid waste from the drainage system to lessen its blockage. This project helped Brgy. North Fairview Quezon City to lessen the solid waste in the drainage system that causes overflow of water in the drainage. To develop the project, the researchers employed quantitative research through questionnaires and surveys or by manipulating pre-existing statistical data using computational techniques. The data gathered came from the survey questionnaire to prove the accuracy of the project. The study utilized randomly selected fifty (50) respondents who live near the creek area of Metro Manila, Philippines. The researchers found that the health and safety of people near creeks are important because the project had the capability for proper waste removal, not only protecting the public but also safeguarding the environment from the harmful effects of solid waste. The overall average of the weighted mean is four point five (4.5), a highly acceptable; therefore, it was interpreted that there is a significant relationship between the system and the security and safety of living. The researchers found out that the project is easy to use, efficient, maintainable, and with cost cost-savings. The researchers created a device that can help those streets in Metro Manila. The device has various benefits. It removes waste from running water in drainage, and also, by using a sensor, it can detect the waste. If the device works, waste can now be removed from the drainage for the meditation of the conveyor, and the waste can be taken to the trash can. Help lessen waste in drainage by separating solid waste.